A guide to better punctuation - "Burt, Angela" (Stanley Thornes: Cheltenham, 1991)
This revised edition on the use of punctuation in the English language has been prepared to meet the requirements of the National Curriculum at Key Stages 3 and 4, while continuing to be of help to sixth-form and college students.
Keywords: English language Punctuation